Associations between dairy and alcohol consumption and major depressive disorder in a mendelian randomization study - Dan Qiu; Renjie Song; Xuejing Cao; Yucheng Tian; Xue Cheng; Dongqing Sun; Shaomin Cai; Zhaowei Wang; Weijia Zhang (Scientific Reports, 2024)
Abstract This study explored the link between diet and major depressive disorder (MDD) to provide fresh insights for MDD prevention. Single nucleotide polymorphisms (SNPs) associated with common foods, such as meat, bread, cheese, fruits, cereals, vegetables, and four alcohol intake categories, were leveraged as instrumental variables. Accordingly, this study employed the inverse variance weighting (IVW) method to evaluate the genetically predicted associations of different food phenotypes with MDD risk. The sensitivity analysis involved MR‒Egger regression and Mendelian random polymorphism residuals, along with outlier tests, to assess instrumental variable pleiotropy. Additional analysis methods, such as MR‒Egger, the weighted median method, and the weighted model, were used to validate the robustness and reliability of the findings. The results of the univariable Mendelian randomization(UVMR) analysis using IVW indicated that genetically predicted consumption of cheese [OR = 0.841, 95% CI: 0.737–0.959, P = 0.0099], dried fruit [OR = 0.7922, 95% CI: 0.644–0.973, P = 0.0264], beer [OR = 1.284, 95% CI: 1.026–1.608, P = 0.0291], and spirits [OR = 3.837, 95% CI: 1.993–7.387, P = 0.0001] were significantly associated with the risk of developing major depressive disorder. Specifically, cheese and dried fruit intake exhibited a inverse correlation with MDD risk, whereas beer and spirits intake showed a positive correlation, with spirits showing a stronger positive correlation. Fourteen other foods, including meat, vegetables, fruits, red wine, and white wine, displayed no significant association with the occurrence of major depression through either type of alcohol intake. In the multivariable Mendelian randomization(MVMR) analysis, considering potential confounding factors such as insomnia, smoking, and the use of contraceptive pills, cheese was identified to have an independent causal relationship with MDD (OR: 0.754, 95% CI: 0.591–0.962, p = 0.0229). No independent causal relationships were identified between dried fruit, beer, or spirits and MDD. The reverse Mendelian randomization (rMR) analysis indicated that MDD did not have a significant effect on the intake of cheese, dried fruit, beer, or spirits, supporting the presence of a unidirectional causal relationship. Finally, the study examined the relationships between dietary characteristics, per capita alcohol intake, and depression incidence among residents of Shanghai, Peking, and Guangdong Provinces of Asian ethnicity in China. These findings align with the conclusions drawn from Mendelian randomization analysis, suggesting that maintaining a diverse diet, sensibly consuming cheese and dried fruit, and reducing beer and spirit intake may prevent MDD.